Inside Cover: An Iodine‐Vapor‐Induced Cyclization in a Crystalline Molecular Flask (Angew. Chem. Int. Ed. 20/2016). Issue 20 (5th April 2016) - Knichal, Jane V.; Shepherd, Helena J.; Wilson, Chick C.; Raithby, Paul R.; Gee, William J.; Burrows, Andrew D.
Abstract : The iodine‐vapor‐induced cyclization of 1, 8‐bis(2‐phenylethynyl)naphthalene (shown on the left) into the corresponding indeno[2, 1‐α]phenalene species (on the right) in the host environment of a zinc‐containing crystalline molecular flask is described by A. D. Burrows and co‐workers in their Communication on page 5943 ff. The cyclization was monitored spectroscopically and found to proceed under mild conditions and without the need to suspend the crystals in solvent.